A Tale of Three Recent Pandemics - Miranda, Mafalda N.S. (2022)
Funding Information: This study was financed by FCT through the following projects: GHTM-UID/04413/2020, INTEGRIV (PTDC/SAU-INF/31990/2017) and the scholarship PD/BD/135714/2018 and MARVEL (PTDC/SAU-PUB/4018/2021). This project has received funding from the European Union’s Horizon Europe Research and Innovation Programme under grant agreement No. 101046016. This work also received funding from the European Research Council (ERC) under the European Union’s Horizon 2020 research and innovation program (PL and AT: grant number 101003688 – EpiPose project). PL gratefully acknowledges support from the Fonds voor Wetenschappelijk Onderzoek (FWO) via postdoctoral fellowship 1242021N and research project G0H0420N, and the Research council of the Vrije Universiteit Brussel (OZR-VUB) via grant number OZR3863BOF. This research acknowledges funding from the Flemish Government through the AI Research Program. Publisher Copyright: Copyright © 2022 Miranda, Pingarilho, Pimentel, Torneri, Seabra, Libin and Abecasis.